Effect of reduced ambient pressure on weld formability, microstructure and corrosion behaviors in laser beam welding of zirconium alloy - Lianfeng Wei; Yumo Jiang; Di Xie; Yong Zheng; Shengkui Zhang; Peicheng Lin; Meng Jiang; Xi Chen; Peng He; Yanbin Chen (Journal of Materials Research and Technology)
Welding zirconium alloys is a critical challenge in the nuclear industry owing to their high sensitivity to hydrogen and oxygen at high temperatures. This study explored the feasibility of vacuum laser welding as an alternative to conventional electron beam welding. The effects of reduced ambient pressure on weld formability, microstructure, and corrosion behavior were investigated. The results indicated a significant increase in the weld penetration depth and aspect ratio as the ambient pressure decreased from 101 kPa to 0.1 kPa. Low-vacuum conditions produced sound welds with improved surface quality and high aspect ratios. The molten pool and keyhole behaviors at different ambient pressures were experimentally and theoretically studied. The results revealed that a reduced ambient pressure transformed the welding process from thermal conductivity welding to deep keyhole welding. A larger molten pool and stable keyhole were observed in low vacuum, whereas atmospheric conditions resulted in a smaller molten pool obscured by bright plasma plumes. Microstructural analysis of welds under atmospheric and low-vacuum conditions revealed the growth of columnar crystals from both sides toward the center. Moreover, larger equiaxed crystals were observed in vacuum-welded joints owing to prolonged exposure to high temperatures, resulting from the increased heat input under low-vacuum conditions. A high-temperature, high-pressure corrosion test demonstrated that oxide film thickness gradually decreased with decreasing environmental pressure. The weld produced at 0.1 kPa exhibited excellent corrosion resistance, forming a black oxide film with good adhesion. This oxide film enhances the corrosion resistance of the weld, making it suitable for nuclear applications.